Prediction of the Risk of Laparoscopy-Assisted Gastrectomy by Comparing Visceral Fat Area and Body Mass Index - Yongke Liu; Dong Guo; Zhaojian Niu; Yuliang Wang; Guanghua Fu; Yanbing Zhou; Qingkai Xue; Xinliang Jin; Zhiqi Gong (Gastroenterology Research and Practice)
Propose. The purpose of this study was to compare the accuracy of visceral fat area (VFA) and body mass index (BMI) in predicting the risk of laparoscopic-assisted gastrectomy. Methods. Clinicopathological and imaging data of 133 patients who underwent laparoscopy-assisted gastrectomy were recorded, including 17 cases of conversion to open surgery. The remaining 116 patients were retrospectively analyzed after we excluded 17 patients who had been transferred to laparotomy. The patients were divided into two groups according to BMI (≤25 kg/m2: BMI-L group; >25 kg/m2: BMI-H group) and VFA (≤100 cm2: VFA-L group; >100 cm2: VFA-H group). Clinical outcomes were compared between the BMI and VFA subgroups. Results. There were no differences in intraoperative blood loss and the number of harvested lymph nodes between low and high patients defined by BMI and VFA (p>0.050). However, in the comparison of patients who underwent laparoscopic resection only, it was found that the operation time and intraoperative blood loss of the VFA-H group were more than those of the VFA-L group (p<0.050). Compared to the VFA-L group, the VFA-H group had later first exhaust time (p=0.018), more complications (p<0.001), and longer hospital stays (p=0.049). However, no similar conclusion was obtained in the BMI group (p>0.050). Conclusion. This study demonstrates that VFA better evaluates the difficulty of laparoscopy-assisted gastrectomy and the risk of postoperative complications than BMI.